Analisis Kualitas Website E-Learning Universitas dengan Metode WebQual 4.0 dan Importance Performance Analysis - Rio Handika; Muhammad Hasbi; Teguh Susyanto (Jurnal Ilmiah SINUS, 2022)
E-learning services are currently needed to support learning activities. Since the coronavirus pandemic, the existence of e-learning is very important for online learning activities. This e-learning service is to facilitate for college who must be learned from home. This makes e-learning need to be measured its effectiveness. The purpose of this research is to analyze the quality of the e-learning website at University using the WebQual 4.0 and the Importance Performance Analysis to find out the gaps and what parts should be prioritized for improvement for better e-learning quality. The variables used are usability, information quality, and service interaction quality. The results of this research are based on the achievement value, the quality of usability variable is 80% (very good), information quality is 80% (very good) and service interaction is 79% (good). Gap analysis produces an overall gap value of (- 0.30) which means that the quality of e-learning is not in accordance with user expectations. From quadrant analysis, it is found that the indicators regarding interaction with the website are obvious and easy to understand, the website appearance is attractive, and security of user's private information is included in quadrant I, which means that these indicators are the first priority for improvement of the e-learning website of University.